Origen de los manantiales de La Costa Verde - Rojas, Rubén (2019)
This paper tries to determine the origin of springs on the beach Costa Verde, located in the district of Barranco, Miraflores and Magdalena province of Lima, Peru. These springs, near and at sea level, survive the process of urbanization of agricultural land, started in the early 70s, which decreased the water table aquifer of Lima, and wiped the water leaks into the cliffs. To identify the source isotope physical, chemical and bacteriological of samples taken from five springs analysis has been carried out. The conductivity and temperature, measured in situ, are similar to those obtained on Lima aquifer waters. The laboratory analysis showed no significant signs of total or fecal coliform, discarding possible leakage from sewerage Lima. The water isotopic concentrations on springs differ from the average obtained on Lima aquifer waters, recharged by infiltration of the Rimac River. These results suggest that the water from the springs of Costa Verde come from a direct recharge in the basin of the river, due to infiltration of rainfall or river at an altitude of about 3600 m.